Risks of Ruxolitinib in STAT1 Gain-of-Function-Associated Severe Fungal Disease. (22nd September 2017) - Zimmerman, Ofer; Rösler, Berenice; Zerbe, Christa S; Rosen, Lindsey B; Hsu, Amy P; Uzel, Gulbu; Freeman, Alexandra F; Sampaio, Elizabeth P; Rosenzweig, Sergio D; Kuehn, Hye Sun; Kim, Tiffany; Brooks, Kristina M; et al.
Abstract: Heterozygous STAT1 gain-of-function (GOF) mutations are associated with chronic mucocutaneous candidiasis and a broad spectrum of infectious, inflammatory, and vascular manifestations. We describe therapeutic failures with the Janus Kinase (JAK) inhibitor ruxolitinib in 2 STAT1 GOF patients with severe invasive or cutaneous fungal infections.